Letter from Henry M. Baker to Margaret M. Booth - Baker, Henry M. (1893)
Henry M. Baker writes to Margaret M. Booth née Cardeza. Baker was the attorney representing Mrs. Booth's case for a relief bill, but at the time of this letter, had become an elected member of Congress. Baker blames the representatives from Pennsylvania for the failure of the relief bill in the House and recommends a new attorney to Booth, S. R. Bond, who will represent her under the same terms and conditions as Baker had done.
Keywords: Booth, James Curtis, 1810-1888; Bills, Legislative; Martinez Cardeza, Margaret; Mint of the United States; United States Mint